Characterization of anodic growth and dissolution of antimony oxide films - Linarez Pérez, Omar Ezequiel (2009)
The anodic growth, morphology and stability of antimony oxide films grown in buffered phosphate electrolytes has been characterized by electrochemical methods, in situ ellipsometry and atomic force microscopy. The anodic voltammetric behaviour for the growth of antimony oxide films at low potentials can be interpreted as the stepwise electroformation of different antimony species with formation of soluble species up to give Sb2O3. This is followed by the anodic film growth at higher potentials through an ionic conduction mechanism caused by a 'high field', which drives the ionic migration as in typical "valve" metals. Ellipsometric results indicate that anodic films dissolve in the electrolysis media. Anodic Sb2O3 films are anisotropic, with complex refractive indices lower than those of crystalline antimony oxides. This is ascribed to hydration, anions incorporation or lack of crystalline structure in anodic oxides. The electric field strength obtained from the thickness/potential dependence, results 2.25 × 106 V cm-1, which also supports that anodic Sb2O3 growth takes place by an ionic current driven by a high electric field within the oxide film. Morphology of anodic Sb2O3 films obtained by AFM shows that surfaces are smooth and flat and films are pore-free. The grain texture depends on concentration of electrolyte as a consequence of a different chemical dissolution rate. The stability of passive antimony oxide films at open circuit was analyzed by cyclic voltammetry with either constant or increasing anodic switching potentials. The overall growth and dissolution of antimony oxide films is described in terms of the oxide film growth by the high-field migration model coupled with a homogeneous dissolution process. The parameters A and β in the equation i = A exp (βε) that characterize the dependence between current growth and field strength in the high-field growth as well as dissolution current for different conditions are obtained. Dissolution current dependence with electrolyte properties, indicate that antimony oxide dissolution is promoted by phosphate ions and is almost independent of pH. © 2009 Elsevier B.V. All rights reserved.